Le rôle de la réglementation dans la protection des milieux aquatiques. Le cas de l’autosurveillance des réseaux d’assainissement urbain en France - Selma Baati; Sophie Vareilles; Jean-Yves Toussaint (VertigO)
This article focuses on socio-technical changes in the current context of climate changes: in particular, it examines regulations' role in accomplishing those changes. For this reason, it focuses on the regulations implemented to protect aquatic environments in France through the analysis of the self-monitoring procedure for sewerage systems. Thus, this article is based on a study of the legislative and regulatory texts instituting this procedure and is also based on two case studies on the Metropolis of Lyon and Nantes. These cases include in situ observations and interviews with actors involved in the monitoring of sewage networks. They point out the effects of regulations on organizations and on the surveillance implementation of wastewater system discharges into aquatic environments by local authorities. However, monitoring remains limited due to the restricted resources (particularly in terms of personnel) of the local authorities and of the other involved organizations; its sustainability even appears fragile in Nantes’ agglomeration. Under these conditions, monitoring generally fulfills the minimum requirements of regulations (producing data on wastewater system discharges into aquatic environments), but does not meet the environmental objectives that originally led to the procedure (protecting the environment, restoring the quality of aquatic environments).